On several correlation integrals of the deep level transients - Hoang, Nam Nhat (H. : ĐHQGHN, 2017)
This works presents the theoretical study on several correlation integrals of the capacitance transients of the deep levels. The deconvolution of the transient signals was the major subject of the number of methods referred to under the common name as the Deep Level Transient Spectroscopy methods. In general the separation of the overlapping exponential decays C(t) does not provide a unique solution, so the detection of the closely spaced deep levels by these transients should base mainly on the temperature dependence C(T), not only on the C(t). The results show that the average emission factor en is obtainable directly from various correlation integrals of the capacitance transients and the average activation energy E of the deep levels is detectable via the shift operators of the transients according to the temperature. A new scanning technique is suggested.